The Influence Of Brand Image, Promotion And Product Quality On Purchase Decisions For Ardeponds Indonesia (Case Study Of Ardeponds Indonesia Skincare In Pulogadung District) - Yusuf Suhardi; Dadang Munandar; Dian Surya Sampurna; Meita Pragiwani; Diana Diana (International Journal of Artificial Intelligence Research, 2024)
The aim of this research is to determine the influence of brand image, promotion and product quality on purchasing decisions at Ardepons Indonesia in Pulogadung District, Jakarta. The research used is quantitative with the research strategy used by researchers being an associative strategy. This research uses primary data by distributing questionnaires to 97 Ardepons user respondents. The sampling technique used was non-probability sampling. The data processing method in this research uses validity testing, reliability testing, partial and simultaneous determination. This research tests the hypothesis using the SPSS Version 25 application. The results of this research show that the processing results areBrand image has a positive and significant effect on Ardepons purchasing decisions. Promotions have no effect on purchasing decisions for the Ardepons brand. Product quality has a positive and significant effect on purchasing decisions. Brand image, promotion and product quality simultaneously have a positive and significant effect on purchasing decisions for Ardepons Cosmetics.